Booms, Busts, and Fraud - Povel, Paul; Singh, Rajdeep; Winton, Andrew (Review of Financial Studies, 2007)
[Firms sometimes commit fraud by altering publicly reported information to be more favorable, and investors can monitor firms to obtain more accurate information. We study equilibrium fraud and monitoring decisions. Fraud is most likely to occur in relatively good times, and the link between fraud and good times becomes stronger as monitoring costs decrease. Nevertheless, improving business conditions may sometimes diminish fraud. We provide an explanation for why fraud peaks towards the end of a boom and is then revealed in the ensuing bust. We also show that fraud can increase if firms make more information available to the public.]